ANALISIS UNSUR INTRINSIK PADA NOVELET MY DREAM MARRIED LIFE SEBAGAI REPRESENTASI BUDAYA POPULER DALAM FIZZO NOVEL - Fauzi, Nurul; Firdaus, Asep; Suparman, Fauziah (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research literature with the title Intrinsic Element Analysis In the Novelette My Dream Married Life As A Representation Of Popular Culture In Fizzo Novel. This research discusses the intrinsic elements in the novelette My Dream Married Life and reflection of popular culture in novelette which is studied through the sociology of literature. In the sociology of literature, there is one important part, namely the reflection of era which is the main topic of this research. This research uses descriptive qualitative method. The results of the analysis in this study are that the novelette My Dream Married Life has the theme of wedding dreams. Then, it has a main character named Alea. There is a mixed flow characterized by past and present plots. The second formulation of the problem regarding the reflection of popular culture in the novelette My Dream Married Life is that there are six cultures, including: relativism, pragmatism, popularity, hybrid, consumerism culture, and visual culture.